Intensive site preparation for reforestation wastes multi-trophic biodiversity potential in commercial oak woodlands. (15th December 2021) - Košulič, Ondřej; Procházka, Jiří; Tuf, Ivan H.; Michalko, Radek
Abstract: Lowland oak forests host high biodiversity throughout Europe, and to maintain their high biodiversity potential we need to understand how current silviculture practices influence these ecosystems. The most common harvest approach in oak woodlands remains clear-cutting followed by site preparation for reforestation. The site preparation can vary in intensity and possibly affect forest biodiversity in various ways. We studied the impact of site preparation intensity on ground-dwelling arthropod predators and detritivores in commercial oak woodlands. The intensive management included mechanical site preparation with soil milling, stump removal, and herbicide application. The extensive management consisted of natural succession after reforestation with only such slight disturbances as regular hand-provided mowing of vegetation. We recorded 120 spider species, 92 species of ground beetles, 10 species of centipedes, 17 species of millipedes, and 7 species of woodlice, including a relatively large number of threatened species. We found that intensive post-logging management strongly homogenized the habitat structure, and this led to low multi-trophic taxonomic and functional diversity in comparison to that under extensive management. At sites with extensive management, there was not only high functional diversity but also high functional redundancy. Species of conservation concern almost vanished from clearings under intensive management. The high multi-trophic diversity and functional redundancy indicate that extensive site preparation may enhance ecosystem multi-functionality, including primary productivity and ecosystem resilience. Extensive post-harvest management is therefore strongly preferable, and it is also economically more feasible. Intensive post-harvest management should be prohibited in lowland forests within transition zones to localities under nature protection or in natural oak forests. Highlights: The effect of management practices on oak forest arthropods was studied. Intensive post-logging management strongly homogenized the habitat complexity. Soil milling significantly decreased taxonomic and functional multi-trophic diversity. Species of conservation concern diminished in forest clearings under soil milling. Extensively managed clearings can enhance biodiversity of commercial forests.